ERBB3 overexpression due to miR-205 inactivation confers sensitivity to FGF, metabolic activation, and liability to ERBB3 targeting in glioblastoma - Francesca De Bacco; Francesca Orzan; Jessica Erriquez; Elena Casanova; Ludovic Barault; Raffaella Albano; Antonio D’Ambrosio; Viola Bigatto; Gigliola Reato; Monica Patanè; Bianca Pollo; Geoffrey Kuesters; et al. (Cell Reports, 2021)
Summary: In glioblastoma (GBM), the most frequent and lethal brain tumor, therapies suppressing recurrently altered signaling pathways failed to extend survival. However, in patient subsets, specific genetic lesions can confer sensitivity to targeted agents. By exploiting an integrated model based on patient-derived stem-like cells, faithfully recapitulating the original GBMs in vitro and in vivo, here, we identify a human GBM subset (∼9% of all GBMs) characterized by ERBB3 overexpression and nuclear accumulation. ERBB3 overexpression is driven by inheritable promoter methylation or post-transcriptional silencing of the oncosuppressor miR-205 and sustains the malignant phenotype. Overexpressed ERBB3 behaves as a specific signaling platform for fibroblast growth factor receptor (FGFR), driving PI3K/AKT/mTOR pathway hyperactivation, and overall metabolic upregulation. As a result, ERBB3 inhibition by specific antibodies is lethal for GBM stem-like cells and xenotransplants. These findings highlight a subset of patients eligible for ERBB3-targeted therapy.